Eco-Friendly Hydrogels Loading Polyphenols-Composed Biomimetic Micelles for Topical Administration of Resveratrol and Rutin - Beatriz N. Guedes; Tatiana Andreani; M. Beatriz P. P. Oliveira; Faezeh Fathi; Eliana B. Souto (Biomimetics)
In this study, we describe the development of hydrogel formulations composed of micelles loading two natural antioxidants—resveratrol and rutin—and the evaluation of the effect of a by-product on the rheological and textural properties of the developed semi-solids. This approach aims to associate the advantages of hydrogels for topical administration of drugs and of lipid micelles that mimic skin composition for the delivery of poorly water-soluble compounds in combination therapy. Biomimetic micelles composed of L-α-phosphatidylcholine loaded with two distinct polyphenols (one non-flavonoid and one flavonoid) were produced using hot shear homogenisation followed by the ultrasonication method. All developed micelles were dispersed in a carbomer 940-based hydrogel to obtain three distinct semi-solid formulations, which were then characterised by analysing the thermal, rheological and textural properties. Olive pomace-based hydrogels were also produced to contain the same micelles as an alternative to respond to the needs of zero waste and circular economy. The thermograms showed no changes in the typical profiles of micelles when loaded into the hydrogels. The rheological analysis confirmed that the produced hydrogels achieved the ideal properties of a semi-solid product for topical administration. The viscosity values of the hydrogels loaded with olive pomace (hydrogels A) proved to be lower than the hydrogels without olive pomace (hydrogels B), with this ingredient having a considerable effect in reducing the viscosity of the final formulation, yet without compromising the firmness and cohesiveness of the gels. The texture analysis of both hydrogels A and B also exhibited the typical behaviour expected of a semi-solid system.